Mineral wealth versus resource curse - the stage is set - Motlhabane, Kutlwano (Graduate School of Business (GSB), 2019)
The debate regarding the impact of resource wealth being a curse rather than a benefit has been a subject of debate since the 1950’s. Only since Sachs and Warner, (1995) the ground-breaking study which confirmed a negative relationship between resource abundance and economic growth for a selected set of countries there has been a narrative termed the ‘natural resources hypothesis’. This hypothesis asserts that countries with natural resource abundance tend to grow at a slow economic rate than countries with less resource abundance. Africa, being the most resource abundant continent compared to all other continents should be the best illustrator of the hypothesis because of vast mineral wealth coupled with the high level of poverty on the continent. This study seeks to determine if African citizens are on average deemed better or worse off given the abundant natural resources endowed in most African countries in relation to quality of life and income inequality as a measurement tool. The study further examines the effect of resource abundance in African countries, using income inequality as an addition variable above the economic growth. Using a panel data fixed effect estimation model for African countries and Middle East countries from 1970 to 2016, the study finds the existence of a U-shaped relationship between resource rent and income inequality, which supports the literature regarding the Kuznets curve. The study also found that rising consumer price inflation significantly worsens average income inequality within an African country. In addition, a high degree of trade openness significantly reduces income inequality within an African country, if all else is held constant. It is thus concluded that for African countries based on the population level, inflation level, degree of trade openness, and GDP share of domestic savings, accumulation of more coal rents share is expected to worsen average income inequality, while more mineral resource rents share reduces income inequality. The study recommends that African countries should find ways to measure inequality in their respective countries which would better illustrate the general relationship between mineral wealth and income inequality. Equally valuable would be the investment in research such as studies and reports which that would track the distribution of income over time in countries undergoing a mineral boom.